Factors Influencing Stockouts of Vital Category Drugs in the Pharmacy Facility, 2024 - Oqui, Maximiano; Corte-Real de Araújo, Artur Natalino; Esco-rial de Jesus Fernandes, Egia Clara da Costa; Evaristo Obeno, Olandino; Paicheco, Rosa; Freitas Moreira, Adriano (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Stockouts of vital medicines remain a critical issue in hospitals, particularly when drug availability drops to zero in pharmacy facilities. Although supplies may still exist elsewhere, it often takes up to a week for replenishment, potentially jeopardizing patient care. The "vital" category includes life-saving drugs whose unavailability is unacceptable. In Timor-Leste, stockout rates reported by the Ministry of Health were 20% in 2020, 22% in 2021, 19% in 2022, and rose sharply to 43% in 2023. Objective: This study aims to identify the factors contributing to stockouts of vital medicines at the Guido Valadares National Hospital (HNGV) Pharmacy Facility. Method: One of the methods used in this research is a quantitative analytical approach with a cross-sectional study design. The sampling technique employed is probability sampling, which approximates the total sample. Data analysis was conducted using the SPSS program to perform a Spearman Rank Correlation. Result and Discussion: Results revealed that human resources (p = 0.00, r = 0.416), medicine management (p = 0.00, r = 0.472), and patient volume (p = 0.00, r = 0.600) significantly influence stockouts. Conclusion: To eliminate the problem of stockouts in Timor-Leste, health professionals must pay attention to the factors influencing stockouts. Additionally, professional medication control services should plan medication purchases before supplies run out.